Regulation and Structuring of Budgeting Process in Commertcial Organization as Factor of Providing Effectiveness of Budgeting Subsystem - S. V. Asriev; T. O. Nazarova; I. A. Pavlenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Important components of effective organization of budgeting subsystem in commercial structures are clear definition of norms and rules of its building, identification of its place and role in the information system of management support and fixing clear-cut, comprehensive regulation of carrying-out concrete steps for each responsible employee. The authors found certain aspects of the present problem, which require well-grounded specification. After studying regulation and structuring of budgeting, a conclusion was drawn that budgeting is not only expedient but necessary for budget in order to guarantee its safe and sustainable development. Criteria idea of the fact when budgeting can be expedient for business is presented in the article. Specifications concerning periods of budgeting in view of certain indicators (budgeting items) are also provided. The authors show advantages and drawbacks of the important element of budgeting regulation, i.e. building mechanism of employees’ motivation in budgeting subsystem itself. On the basis of their own experience in the field of enterprise economics and in result of summarizing expert opinions they formulate problems, which should be taken into account in developing budget regulation in the company.